2011
DOI: 10.1016/j.tibtech.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-associated molecular patterns on biomaterials: a paradigm for engineering new vaccines

Abstract: Vaccine development has progressed significantly and has moved from whole microorganisms to subunit vaccines that contain only their antigenic proteins. Subunit vaccines are often less immunogenic than whole pathogens; therefore, adjuvants must amplify the immune response, ideally establishing both innate and adaptive immunity. Incorporation of antigens into biomaterials, such as liposomes and polymers, can achieve a desired vaccine response. The physical properties of these platforms can be easily manipulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
123
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 136 publications
1
123
0
5
Order By: Relevance
“…The particulate nature of these delivery vehicles permits their rapid internalization by DCs and their composition can provide adjuvant properties required for immunogenicity. 18 Ag encapsulated in NPs and targeted to APC are protected from enzymatic degradation, and processed and presented to T lymphocytes after their delivery to the APC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The particulate nature of these delivery vehicles permits their rapid internalization by DCs and their composition can provide adjuvant properties required for immunogenicity. 18 Ag encapsulated in NPs and targeted to APC are protected from enzymatic degradation, and processed and presented to T lymphocytes after their delivery to the APC.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Moreover, the particulate nature of these systems permits their rapid internalization by DCs, perhaps due to their pathogen-mimicking size and charge profile, an effect that can be heightened by surface decoration of NPs with defined PAMP. 18 However, comparatively little is known about whether immune responses induced by NPs can be further enhanced by directing Ag-containing NPs via cell surface lectin receptors such as DEC-205 to human monocyte-derived DCs, the principal cell type utilized clinically in antitumor vaccination. It is understood that the presence and density of anti-DEC-205 on NPs in the mouse system can enhance a vaccine response, 19 but outside of recent targeting of plasmacytoid DCs as APC, 9 very little is known regarding the efficiency of this targeted approach and its mechanistic impact on cross-presentation in human DC populations.…”
Section: Introductionmentioning
confidence: 99%
“…The particulate nature of PLGA particles performed a rapid internalization, perhaps because of its pathogen-mimicking size and charge profile. 28 The studies by Newman et al 29 showed that PLGA particles are able to induce and enhance immune responses of poor immunogens. For a viral vaccine, this very interesting study showed that HIV p24 protein adsorbed onto the surface of surfactant-free anionic poly(d,l-lactide) or poly lactic acid nanoparticles was efficiently taken up by mouse dendritic cells, inducing the maturation of dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the nature of non-viral carriers allows their functionalization with moieties permitting specific targeting to DCs. Additionally they allow co-delivery of immunostimulatory molecules which can direct the immune system toward the humoral or cellular arm [181]. The simultaneous delivery of antigens and immune-stimulators to the same DC is a feature which has been reported to significantly augment the strength of the induced adaptive immune responses [182][183][184].…”
Section: The Way Forward: Antigen Delivery By Non-viral Carriersmentioning
confidence: 99%